2015
DOI: 10.1080/16506073.2015.1042989
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Core Beliefs and their Relation to Generalized Anxiety Disorder

Abstract: Research has demonstrated that individuals with generalized anxiety disorder (GAD) hold unhelpful beliefs about worry, uncertainty, and the problem-solving process. Extant writings (e.g., treatment manuals) also suggest that other types of maladaptive beliefs may characterize those with GAD. However, these other beliefs have received limited empirical attention and are not an explicit component of cognitive theories of GAD. The present study examined the extent to which dysfunctional attitudes, early maladapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 68 publications
(84 reference statements)
3
18
0
1
Order By: Relevance
“…The results mainly support the general factor NPO being positively correlated with depression, anxiety, and stress. This finding is similar to those of previous clinical studies that supported the important role of NPO in the development of anxiety and depressive disorders (Fergus et al, 2015;Koerner et al, 2015;Hearn et al, 2017). Moreover, this study also showed that the domain-specific factor of perceived threat was positively related to engagement with worry, and both self-inefficiency and negative outcome expectancy were positively associated with the general factor of worry.…”
Section: Discussionsupporting
confidence: 91%
“…The results mainly support the general factor NPO being positively correlated with depression, anxiety, and stress. This finding is similar to those of previous clinical studies that supported the important role of NPO in the development of anxiety and depressive disorders (Fergus et al, 2015;Koerner et al, 2015;Hearn et al, 2017). Moreover, this study also showed that the domain-specific factor of perceived threat was positively related to engagement with worry, and both self-inefficiency and negative outcome expectancy were positively associated with the general factor of worry.…”
Section: Discussionsupporting
confidence: 91%
“…The associations between EMS and a wide range of mental-health problems have been investigated extensively, both in adult and-more recently-in adolescent samples. For example, core maladaptive schemas have been successfully identified in adult patients suffering from various forms of psychopathology including personality disorders (Barazandeh, Kissane, Saeedi, & Gordon, 2016), substance misuse (Brotchie, Meyer, Copello, Kidney, & Waller, 2004;Shorey, Stuart, & Anderson, 2013), aggression-related disorders (Baker & Beech, 2004), anxiety disorders (Koerner, Tallon, & Kusec, 2015), depression (Renner, Lobbestael, Peeters, Arntz, & Huibers, 2012), eating disorders (Unoka, Tölgyes, Czobor, & Simon, 2010), and post-traumatic stress disorder (Cockram, Drummond, & Lee, 2010). With regard to adolescents, EMS were also found to be related to a variety of psychological symptoms in community adolescents (Roelofs, Lee, Ruijten, & Lobbestael, 2011), referred and nonreferred depressed adolescents (Lumley & Harkness, 2007), referred obese youth (van Vlierberghe & Braet, 2007), and referred youth with various emotional and behavioural problems (van Vlierberghe, Braet, Bosmans, Rosseel, & Bögels, 2010).…”
Section: Early Maladaptive Schemasmentioning
confidence: 99%
“…Furthermore, Overvigilance/Inhibition and Other-Directedness domains have been shown to have a central role in the activation of the cognitive trait anxiety. 55 In fact, maladaptive cognitive schemas related to perfectionism, such as Unrelenting Standards schema, Self-Sacrifice, and Negativity schema, characterize people who are prone to excessive and pathological worry and uncertainty in the problem-solving process. 55 …”
Section: Introductionmentioning
confidence: 99%